Fashioning gothic bodies - Spooner, Catherine (Manchester University Press, 2017)
This innovative book is the first to make an explicit link between constructions of the body in Gothic literature and film and historically specific fashion discourse, from the 1790s to the 1990s.
Formerly CIP.
Dedication Acknowledgements List of figures 1. Curtain'd in mysteries: An introduction to Gothic fashion 2. Revolution and revealment: The Gothic body and the politics of décolletage 3. Clothes made the man: Fashioning the self in Victorian Gothic fiction 4. Mysteries of the visible: Dandies, cross-dressers and freaks in late-Victorian Gothic 5. Cosmo-Gothic: The double and the single woman 6. Undead fashion: Nineties style and the perennial return of Goth 7. Refashioning Gothic bodies: An anti-conclusion Bibliography Fashion spreads Film and visual media Selected discography Selected electronic sources.
Available through ManchesterHive.
Keywords: Horror tales, English -- History and criticism.; Gothic revival (Literature) -- Great Britain -- History.; Clothing and dress in literature.; Costume -- Great Britain -- History.; Fashion -- Great Britain -- History.; Récits d'horreur anglais -- Histoire et critique.; Littérature frénétique -- Grande-Bretagne -- Histoire.; Fashion & Society.; DESIGN / Textile & Costume.; Costume.; Fashion.; Gothic revival (Literature); Horror tales, English.; Great Britain.; Criticism, interpretation, etc.; History.